2015
DOI: 10.1093/molbev/msv041
|View full text |Cite
|
Sign up to set email alerts
|

Nonadaptive Amino Acid Convergence Rates Decrease over Time

Abstract: Convergence is a central concept in evolutionary studies because it provides strong evidence for adaptation. It also provides information about the nature of the fitness landscape and the repeatability of evolution, and can mislead phylogenetic inference. To understand the role of adaptive convergence, we need to understand the patterns of nonadaptive convergence. Here, we consider the relationship between nonadaptive convergence and divergence in mitochondrial and model proteins. Surprisingly, nonadaptive con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
153
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(168 citation statements)
references
References 40 publications
13
153
1
Order By: Relevance
“…This is precisely what would be expected if the entrenchment observed in our simulations occurs in nature. Similarly, Goldstein et al (90) studied the probability of parallel evolution along two lineages as a function of the evolutionary distance between those two lineages. They found that the larger the evolutionary distance between the two lineages, the lower the rate of convergent evolution.…”
Section: Discussionmentioning
confidence: 99%
“…This is precisely what would be expected if the entrenchment observed in our simulations occurs in nature. Similarly, Goldstein et al (90) studied the probability of parallel evolution along two lineages as a function of the evolutionary distance between those two lineages. They found that the larger the evolutionary distance between the two lineages, the lower the rate of convergent evolution.…”
Section: Discussionmentioning
confidence: 99%
“…If the model and parameter values used are exactly correct, and if all possible reconstructions are considered in the averaging, the AWP method will recover the correct base compositions in the ancestral nodes. Note that AWP is very similar to the approach of sampling ancestral reconstructions according to their posterior probabilities (Williams et al 2006;Goldstein et al 2015); indeed, averaging over all possible ancestral reconstructions (AWP) is equivalent to sampling if the number of samples is infinite. Used to count substitutions along a branch, the AWP method may suffer from two sources of errors.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, they tend to be located at exposed positions to an extent comparable to divergent substitutions ( Fig. 3c), despite the prediction that more exposed positions result in lower convergence probability 28 . Exposed sites are structurally less constrained, and substitutions in such sites are likely to change their interactions with other molecules in solution, rather than changing protein conformation [25][26][27] .…”
Section: Articles Nature Ecology and Evolutionmentioning
confidence: 90%
“…10). Substitution pairs that result in the same descendant amino acid at the same alignment position in both branches were categorized as convergent changes, whereas the remaining substitution pairs were counted as divergent changes 21,28 .…”
Section: Nature Ecology and Evolutionmentioning
confidence: 99%